(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Capital structure is one of the most complex areas of financial decision making because of its inter-relationship with other financial decision variables. Poor capital structure decisions can result in a high cost of capital which decreases the value of a firm. Effective capital structure decisions decrease the cost of capital and hence the value of a firm increases. The objective of this empirical study is to analyze the factors affecting capital structure of sugar industry in Pakistan and to check whether the results confirm or not pecking order theory and trade-off theory. Different theories of capital structure have been reviewed like Modigliani and miller theory, trade-off theory, pecking order theory and market timing theory to make assumptions regarding capital structure of sugar firms. The findings are based on empirical results using panel data techniques for a sample of 30 firms listed on Karachi Stock Exchange from 2008-2011. The results show that tangibility is positively associated with leverage whereas size of the firm and liquidity are negatively associated with leverage. The results of profitability and growth opportunities are insignificant.